(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Obesity is a chronic disease characterized by excess accumulation of body fat, which poses a health risk and is a major risk factor for a number of other chronic diseases, including type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). Obesity is a multifactorial condition whose development involves, in addition to an imbalance between energy intake and expenditure, various neurohumoral mechanisms and environmental factors. A high-calorie diet and a sedentary lifestyle are among the most important causes of obesity [1].